Why is it (Un-)ethical? Comparing potential European partners: A western Christian and an eastern Islamic country - On arguments used in explaining ethical judgments - ARZOVA, SABRİ BURAK (SPRINGER, 2007)
Located at the crossroads of the Eastern and Western world, Turkey today is characterized by a demographically versatile and modernizing society as well as a rapidly developing economy. Currently, the country is negotiating its accession to the European Union. This article yields some factual grounding into the ongoing value-related debate concerning Turkey's potential EU-membership. It describes a mixed-methodology study on moral reasoning in Austria and Turkey. In this study, the arguments given by individuals when evaluating ethically problematic situations in business were compared. Although there were major consistencies, a number of differences were found. These differences, however, were not in the substance (categories) of arguments used but in their relative frequency. Overall, our findings suggest that young, well-educated urban individuals from Western Christian and Eastern Islamic countries are highly consistent in their moral reasoning.
Keywords: cross-cultural comparison; moral reasoning; empirical study; mixed methodology; CONSUMER ETHICS; BUSINESS ETHICS; DECISION-MAKING; ORGANIZATIONAL COMMITMENT; UNITED-STATES; ATTITUDES; BELIEFS; CULTURE; VALUES; SALESPEOPLE